Preharvest calcium chloride sprays affect ripening of Eksotika II’papaya fruits during cold storage - Madani, Babak; Tengku Muda Mohamed, Mahmud; Watkins, Christopher B.; Kadir, Jugah; Awang, Yahya; Shojaei, Taha Roodbar (Elsevier, 2014)
The effects of preharvest application of calcium chloride on ripening, activity patterns of pectin modifying enzymes and overall quality of papaya (Carica papaya L. cv. ‘Eksotika II’) fruits have been investigated. Foliar sprays of 0, 0.5%, 1%, 1.5% and 2% (w/v) calcium chloride were applied six times during the growing season. After harvest, fruits were stored at 12 °C for up to three weeks. Higher calcium concentrations in the sprays coincided with increasing calcium concentrations in peel and pulp tissues, higher firmness and titratable acidity, and reduced respiration rate, ethylene production and soluble solids concentrations, compared with those of the untreated control fruits. The overall quality of fruits treated with calcium was greater than the control fruits. Also, fruits sprayed with calcium had decreased activities of polygalacturonase (PG) and pectin methyl esterase (PME) during storage. Microscopic results confirmed that the middle lamallae of cell walls was more intact in calcium chloride-treated fruits.